Comparative study between Salkowski reagent and chromatographic method for auxins quantification from bacterial production - Guardado-Fierros, Beatriz G.; Tuesta-Popolizio, Diego A.; Lorenzo-Santiago, Miguel A.; Rodriguez-Campos, Jacobo; Contreras-Ramos, Silvia M. (Frontiers in Plant Science, 2024)
The Salkowski reagent method is a colorimetric technique used to determine auxin production, specifically as indole-3-acetic acid (IAA). It was developed to determine indoles rapidly; however, it does not follow Beer's law at high concentrations of IAA. Thus, there could be an overestimation of IAA with the Salkowski technique due to the detection of other indole compounds. This study aims to compare the Salkowski colorimetric method versus a chromatographic method to evidence the imprecision or overestimation obtained when auxins, such as indole-acetic acid (IAA), are determined as traits from promoting growth plant bacteria (PGPB), using ten different strains from three different isolation sources. The analysis used the same bacterial culture to compare the Salkowski colorimetric and chromatographic results. Each bacterium was cultivated in the modified TSA without or with tryptophan for 96 h. The same supernatant culture was used in both methods: Salkowski reagent and ultra-performance liquid chromatography coupled with a Mass Spectrometer (LC-MS/MS). The first method indicated 5.4 to 27.4 mg L -1 without tryptophan in ten evaluated strains. When tryptophan was used as an inductor of auxin production, an increase was observed with an interval from 4.4 to 160 mg L -1 . The principal auxin produced by all strains was IAA from that evaluated by the LC-MS/MS method, with significantly higher concentration with tryptophan addition than without. Strains belonging to the Kocuria genus were highlighted by high IAA production. The indole-3-propionic acid (IPA) was detected in all the bacterial cultures without tryptophan and only in K. turfanensis As05 with tryptophan, while it was not detected in other strains. In addition, indole-3-butyric acid (IBA) was detected at trace levels (13-16 µg L -1 ). In future works, it will be necessary to determine IAA or other auxins using more suitable sensitive techniques and methodologies.